Economic costs of terminal care for selected non-communicable diseases from a healthcare perspective: a review of mortality records from a tertiary hospital in Nigeria - Adesola Oluwafunmilola Olumide; Amir Shmueli; Olayemi O Omotade; Emmanuel S Adebayo; Temitope O Alonge; Gabriel O Ogun (BMJ Open)
Introduction WHO revealed that morbidity and mortality from non-communicable diseases (NCDs) are on the increase and NCDs accounted for approximately 29% of all deaths in Nigeria in 2016. This study was conducted to estimate the economic cost of selected NCDs—lung cancer, liver cancer and liver cirrhosis. These diseases are known to be associated with key modifiable health risk behaviours (smoking and alcohol use), which are prevalent in Nigeria and often commence during the adolescent years.Methods Data were obtained between 2016 and 2017, from mortality records of patients managed for the selected diseases in the University College Hospital, a major referral centre in Nigeria. Information on costs of treatment, clinic visits, admission and transportation was obtained. Average costs of terminal in-patient care and transportation costs (in 2020 prices) were computed per patient. Costs were converted to the US dollar equivalent using the current official rate of US$1: ₦360.50.Results Twenty-two (out of 90 cases recorded) could be retrieved and all the patients had been diagnosed in the terminal stages of the disease. The average direct costs were ₦510 152.62 (US$1415.13) for an average of 49.2 days of terminal care for lung cancer; ₦308 950.27 (US$857.00) and ₦238 121.83 (US$660.53) for an average of 16.6 and 21.7 days of terminal care for patients managed for liver cancer and liver cirrhosis, respectively.Conclusion The economic costs of each of the diseases were very high. Findings emphasise the need for aggressive efforts to promote primary prevention, improve early diagnosis and provide affordable treatment in view of the fact that the monthly minimum wage is less than US$85.00 and treatment costs are borne out-of-pocket by the generality of the population in Nigeria.